2017
DOI: 10.1002/jez.b.22743
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Role for VEGF Signaling in Specification of Homologous Mesenchymal Cell Types Positioned at Spatially Distinct Developmental Addresses in Early Development of Sea Urchins

Abstract: Comparative studies of early development in echinoderms are revealing the tempo and mode of alterations to developmental gene regulatory networks and to the cell types they specify. In euechinoid sea urchins, skeletogenic mesenchyme (SM) ingresses prior to gastrulation at the vegetal pole and aligns into a ring-like array with two bilateral pockets of cells, the sites where spiculogenesis will later occur. In cidaroid sea urchins, the anciently diverged sister clade to euechinoid sea urchins, a homologous SM c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…We found that the A. filiformis transcriptome has two clear 14 In sea urchin embryos, FGF signalling components are expressed in a 19 complimentary pattern, whereby the fgfr2 receptor is specifically expressed by 20 the skeletogenic mesoderm cells and the fgfa ligand is expressed in overlying 21 ectoderm flanking those cells (31,32). Recent work showed that this pattern of 22 expression is also observed for the VEGF signalling genes in both sea urchin 23 (32)(33)(34) and brittle stars embryos, as well as in sea urchin and sea star 24 juveniles (74,75). It has been suggested that the heterochronic activation of 25 this pathway in sea urchin and brittle star embryos lead to the co-option of the 1 adult skeleton into the larva (74,76), as sea star embryos do not have those 2 genes expressed at the embryonic stage and have no larval skeleton (74).…”
Section: Evolution Of Fgf Signalling and Skeleton Formation In Echinomentioning
confidence: 79%
See 1 more Smart Citation
“…We found that the A. filiformis transcriptome has two clear 14 In sea urchin embryos, FGF signalling components are expressed in a 19 complimentary pattern, whereby the fgfr2 receptor is specifically expressed by 20 the skeletogenic mesoderm cells and the fgfa ligand is expressed in overlying 21 ectoderm flanking those cells (31,32). Recent work showed that this pattern of 22 expression is also observed for the VEGF signalling genes in both sea urchin 23 (32)(33)(34) and brittle stars embryos, as well as in sea urchin and sea star 24 juveniles (74,75). It has been suggested that the heterochronic activation of 25 this pathway in sea urchin and brittle star embryos lead to the co-option of the 1 adult skeleton into the larva (74,76), as sea star embryos do not have those 2 genes expressed at the embryonic stage and have no larval skeleton (74).…”
Section: Evolution Of Fgf Signalling and Skeleton Formation In Echinomentioning
confidence: 79%
“…Perturbation of the vegf3 ligand in the sea urchin interferes with both correct 14 skeletogenic cell migration and skeletal rod formation (32)(33)(34). It seems clear 15 that both of these pathways have essential, often interconnected and non-16 redundant roles in skeletogenesis in the sea urchin embryo.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the embryonic mesodermal GRN is highly similar in all echinoderm classes, regardless of the presence or absence of a larval skeleton (18). Indeed, VEGFR expression is one of the only differences in the mesoderm regulatory state between echinoderm embryos that produce larval skeletons [brittle stars and sea urchins (14,19)] and the sea star embryo, which does not (14,15,(18)(19)(20)(21). Furthermore, VEGFR expression is observed in the adult skeletogenesis centers and VEGF is expressed in the adult supporting cells in all studied echinoderm classes [sea urchin (20) brittle stars and sea stars (19)].…”
Section: Significancementioning
confidence: 99%
“…The double‐negative gate is absent from holothuroid and asteroid embryos, supporting the view that it evolved specifically within the echinoid lineage (McCauley, Wright, Exner, Kitazawa, & Hinman, ; Thompson et al, ). In contrast to the double‐negative gate, the regulation of the skeletogenic pathway by ectodermally derived VEGF appears to be conserved in cidaroids (Erkenbrack & Petsios, ; Gao et al, ). In addition, similarities in the expression patterns of downstream components of the network indicate that common regulatory mechanisms are at work.…”
Section: Evolution Of the Skeletogenic Grn In Echinodermsmentioning
confidence: 99%